Acute lung injury following thermal insult to the skin: A light and transmission electron microscopial study - (:unkn) unknown (URBAN & FISCHER VERLAG, 1999)
Oxygen radicals are involved in the development of burn shock and distant organ injury in animal models of trauma. Neutrophils are likely the source of reactive oxygen metabolites as a result of the systemic inflammatory reaction to a local burn insult. The aim of the present study was to assess the role of neutrophils in the development of lung injury related to second degree skin burn in rats. Rats were decapitated at two hours following burn injury. Lung tissue samples were removed and examined biochemically and histologically. Tissue-associated myeloperoxidase (MPO) activity, which is an index of neutrophil infiltration, was increased considerably in lung tissue at 2 h after burn injury. Disturbance of alveolar structure, intraalveolar hemorrhage and prominent neutrophil infiltration indicated lung parenchymal injury. Ultrastructural examination of the lung revealed that pneumocytes type I, pneumocytes type II and capillary endothelial cells were degenerated. The data presented here suggest that neutrophil accumulation in the lung is involved in pathogenesis of this distant organ after burn injury.
Keywords: lung; thermal trauma; microscopy; LIPID-PEROXIDATION; ACTIVATION; COMPLEMENT; RAT; NEUTROPHILS; DAMAGE